Fabrication Of TiO2 Nanoflowers Powder with Various Concentration Of CTAB - Shamsudin, S.; Ahmad, M. K.; Nafarizal, N.; Soon, C. F.; Rahim, R. A.; Alakendram, D. A/L; Shimomura, M.; Murakami, K. (International Journal of Integrated Engineering, 2020)
Nanostructures titanium dioxide (TiO₂) such as nanoflowers and nanorods have contribute in many application. Among TiO₂ nanostructures, TiO₂ nanoflowers gives high surface area that contribute in good binding properties and reducing internal stress and increasing strength of the ceramics.This paper presents fabrication of TiO₂ nanoflowers powder to overcome the cracking problem in ceramic industry. In this study, fabricated rutile-phased TiO₂ nanoflower powder has been successfully synthesized by using hydrothermal method and the surface morphology, structural properties, and the composition of TiO₂ nanoflower powder also identified. The fabricated TiO₂ are characterized using Field Emission Scanning Electron Microscopy (FESEM) to observe the surface morphology of TiO₂, X-ray Dispersion (XRD) was used to determine the crystallite phase and EDX for element composition in fabricated TiO₂ powder. The synthesized TiO₂ powder was obtained from the reaction between deionized water (DI), hydrochloric acid (HCl), Titanium Butoxide (TBOT) and Cetyltrimethylammonium Bromide (CTAB). The hydrothermal temperature is 150 ̊C with fixed hydrothermal time of 10 hours. The parameters varied is the mass of surfactant used, CTAB. The hydrothermal method is proven suitable to fabricate semiconductor materials due to its advantages that parameters are easily modified and can be performed under closed system with low operational temperature. Increased amount of CTAB used make the gap between the nanorod become closer and stronger. The diffraction peaks of all sample hardly changed, but the intensity for each sample was enhanced as the mass of CTAB used increased. The structure also become well crystallined in rutile phase structure.